2021
DOI: 10.3390/su13063533
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Valorization of Non-Wood Forest Products in Europe: A Quantitative Literature Review

Abstract: This article presents a quantitative review of non-wood forest products (NWFPs) at the regional scale in Europe. A text mining approach was applied to titles, abstracts, and keywords extracted from articles in the Scopus database. Different investigations, such as concept mapping and specificity analyses of textual corpus, were performed. Our search yielded a massive number of NWFP-related papers. Specifically, research was distributed in different countries, being more prevalent in the Mediterranean and Scand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Non-wood forest products are a growing business area in Finland, and their valorization is a major research focus (Sacchelli et al 2021). Based on everyone's rights.…”
Section: Enhanced Product Innovationmentioning
confidence: 99%
“…Non-wood forest products are a growing business area in Finland, and their valorization is a major research focus (Sacchelli et al 2021). Based on everyone's rights.…”
Section: Enhanced Product Innovationmentioning
confidence: 99%
“…(Urry, 2010) In the case of inland and mountain areas there is a wide range of agricultural productions in addition to those coming from the forest. Many authors also highlight the value of non-wood forest products (Lovric et al, 2020) and their role inside of ecosystem services both in terms of cultural heritage (Sacchelli et al, 2021;Pardo-de-Santayana et al, 2007), and in relation to the recreational and therapeutic function of forests (Droli et al, 2021;Kangas & Markkanen, 2001;Sievänen et al, 2004;de Aragón et al, 2011;Pettenella, 2009;Cai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…According to Shrestha et al (2017) while the better-off households have access to forest resources that provide higher income, such as timber, the poorest households only rely on low forest resources such as NTFPs. A quantitative review and analysis of non-wood forest products (NWFPs) in Europe showed that mushrooms, resin, cork and other forest fruits were the common ones being collected and harvested for consumption and sale purposes (Sacchelli et al 2021). In South Africa, over 85% of households benefit economically and domestically from NTFPs such as fuelwood, wild spinaches, wooden utensils, edible fruits, grass hand-brushes, and twig hand-brushes (Shackleton and Shackleton 2004).…”
Section: Introductionmentioning
confidence: 99%